Autogestão na pessoa com doença coronária: Importância da intervenção de enfermagem - Rocha, Ana Luisa; Lima, Ligia; Bastos, Celeste (Ediciones ROL, 2020)
Introduction and objectives: Coronary heart disease is one of the main causes of death in Portugal, especially. It is a chronic illness with a complex therapeutic regimen, and since it is often asymptomatic non-adherence is quite frequent, especially in relation to the non-pharmacological component. The present study aims to: a) characterize patients with coronary disease in relation to cardiovascular risk factors, adherence to non-pharmacological treatment, perceived competence and perception of autonomous support by health professionals b) study if nursing intervention promotes self-management in patients with coronary heart disease. Methodology: This is a descriptive, cross-sectional study and correlational study. The participants were 46 patients with coronary heart disease, from two hospitals in the northern region of Portugal, 45,7 % of which were followed by a nursing consultation. Instruments used were: the Perceived Competence Scale, the Health Care Climate Questionnaire, a questionnaire about non-pharmacological adherence. Results and discussion: Results showed that participants reported a moderate adherence to the non-pharmacological treatment, feel very competent to manage their treatment, and perceive the health climate as supportive of their autonomy. Patients supported by nurses reported higher adherence to non-pharmacological treatment strategies, higher perceived competence and perceived the health care climate as supportive of their autonomy when compared to those attended only by doctors. Conclusions: This study suggests that nursing interventions are important for the promotion of self-management in coronary heart patients, and that these interventions should be focused on perceived competence and the promotion of autonomous motivation.
Self-management in patients with coronary heart disease: importance of nursing intervention
Keywords: Personal autonomy; Selfkmanagement; Coronary disease; Nursing care